Litorihabitans aurantiacus gen. nov., sp. nov., an actinobacterium of the family Beutenbergiaceae isolated from beach sand. Issue 4 (20th February 2019) - Hamada, Moriyuki; Saitou, Satomi; Tamura, Tomohiko
Abstract : A novel actinobacterium, designated HIsM16-52 T, was isolated from beach sand collected from Ishigaki Island in Japan and its taxonomic position was investigated by a polyphasic approach. Strain HIsM16-52 T contained both lysine and ornithine as the diagnostic diamino acids of the peptidoglycan. The predominant isoprenoid quinone was MK-8(H4 ) and the major fatty acids were anteiso-C15 : 0, C16 : 0 and C14 : 0 . The detected polar lipids were phosphatidylglycerol, diphosphatidylglycerol, phosphatidylinositol and two unidentified phospholipids. The DNA G+C content was determined to be 73.4 mol%. Phylogenetic analyses based on 16S rRNA gene sequence comparison revealed that strain HIsM16-52 T fell within the cluster of the family Beutenbergiaceae and formed a reliable cluster with the members of the genus Serinibacter . The highest 16S rRNA gene sequence similarities were obtained to species of the genus Serinibacter (97.8–97.9 %), followed by the genera Miniimonas (97.0 %), Beutenbergia (96.4 %) and Salana (95.9 %). However, strain HIsM16-52 T differed from the members of the genus Serinibacter and the other genera within the family Beutenbergiaceae in terms of chemotaxonomic characteristics. Therefore, strain HIsM16-52 T is concluded to represent a novel genus and species of the family Beutenbergiaceae, for which the name Litorihabitans aurantiacus gen. nov., sp. nov. is proposed. The type strain of L. aurantiacus is HIsM16-52 T (=NBRC 112290 T =TBRC 7759 T ).